An intelligent approach for dynamic load frequency control with hybrid energy storage system. Issue 4 (2nd October 2019) - Vengatesh, R. Pon; Rajan, S. Edward; Sivaprakash, A.
ABSTRACT: One of the important factors to be considered in an electric power system is to maintain the frequency constant, so that power stations run satisfactorily in synchronise among the connected pool of power generation systems. The main purpose of load frequency control (LFC) is to reduce the frequency deviation and net interchange of power flow between electrical power generating units and for achieving steady-state error to be zero. This research paper proposes the way to improve the LFC by employing energy storage systems (battery energy storage systems and superconducting magnetic energy storage (SMES)) during change in load demand. The energy storage devices are acting quickly and they are effectively damp electro mechanical oscillations in a power system. Moreover, they provide storage capacity and the kinetic energy of the generator shares the sudden changes in power requirement. An integrated hybrid BES and SMES energy storage systems along with LFC minimise the deviation of frequency by contribution of additional power requirement. Investigating the performance of the LFC with storage system under step change of load (∆Pd ) has been analysed by employing proportional-integral (PI) and fuzzy logic controller (FLC) for frequency regulation and load tracking. Even, the PI controller attains zero steady-state error in system frequency, it has unsatisfied dynamic (overshoots and settling time) performance followed by disturbances. The mismatch power in the power system makes frequency deviation followed by the change in load demand and electrical power generation and it is balanced by employing of an energy storage system with proper controller. The simulation results are illustrated that the performance of LFC system is enhanced by BES storage system which effectively reduces frequency deviation than SMES system. The comparative analysis has been made for LFC with BES, SMES and hybrid storage system employing FLC and PI controller design also. A significant improvement in the frequency profile has been obtained with FLC controller than PI controller followed by the step load changes.